A Review Stability Studies of Tablet Dosage Forms and Their Influence on Physicochemical Characteristics: A Review - Weka Nabil Ubhayahita Sambarana; Aulya Elsa Safitri; Hasna Aulia Qisthi; Faradila Elsa Anggraeni; Juanita Mulia Mahbubah; Salzha Noor Fajrina Febrianti; Delta Happy Friantina; Sabrina Maharani (Indonesian Journal of Global Health Research, 2026)
Tablet dosage forms generally exhibit better stability compared to liquid formulations; however, stability testing remains essential to evaluate both physical and chemical parameters. This study aimed to compare the stability of tablet formulations under various testing conditions in terms of their physicochemical properties. This study aimed to compare the stability of tablet formulations under various testing conditions in terms of their physical and chemical properties. This study employed a literature review approach. Scientific articles were retrieved from Scopus, ScienceDirect, PubMed, MDPI, Web of Science, and Google Scholar, as well as national databases such as GARUDA and SINTA-indexed journals database using the used keywords such as “tablet,” “formulation,” “optimization,” “stability evaluation,” and “stability studies.” The search covered publications from 2016 to 2026. A total of 2,201 articles were initially identified and then screened based on their relevance to the research topic. The main inclusion criterion was studies focusing on the stability of tablet dosage forms, particularly those evaluating both physical stability (such as hardness, friability, and disintegration time) and chemical stability (including active ingredient content and degradation). Based on these criteria, 8 relevant articles were selected and further analyzed to evaluate the physicochemical stability of tablet formulations. The findings indicate that several tablet formulations experienced deterioration in physical and chemical parameters, including changes in hardness, disintegration time, and decreased active ingredient content. These alterations were primarily associated with changes in excipient properties and interactions with environmental factors such as light exposure and moisture. Furthermore, inappropriate storage conditions contributed to the instability of the formulations. The stability of tablet dosage forms is therefore influenced by both formulation factors and storage conditions. The application of drug–excipient compatibility studies (DECS) and crystallo-co-agglomeration techniques during the formulation stage, along with proper control of temperature and humidity and the use of suitable packaging such as aluminium blisters and silica gel are crucial to maintaining tablet stability during storage.